2020
DOI: 10.1175/jcli-d-19-0812.1
|View full text |Cite
|
Sign up to set email alerts
|

A Feature-Based Approach to Classifying Summertime Potential Vorticity Streamers Linked to Rossby Wave Breaking in the North Atlantic Basin

Abstract: This study examines climatological potential vorticity streamer (PVS) activity associated with Rossby wave breaking (RWB), which can impact TC activity in the subtropical North Atlantic (NATL) basin via moisture and wind anomalies. PVSs are identified along the 2-PVU (1 PVU = 10−6 K kg−1 m2 s−1) contour on the 350-K isentropic surface, using a unique identification technique that combines previous methods. In total, 21 149 individual PVS instances are identified from the ERA-Interim (ERAI) climatology during J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…The simulation is performed with explicit convection at a horizontal grid spacing of 0.125 • (in rotated coordinates, corresponding to approximately 14 km) and with 60 hybrid levels in the vertical. Marsham et al (2013b), Pearson et al (2014, and Pante and Knippertz (2019) showed that explicit convection leads to a more realistic representation of the West African Monsoon already with a relatively coarse model resolution on the order of 10 km. Initial and lateral boundary conditions are provided every 6 h by the isotope-enabled global climate model ECHAM5-wiso (Werner et al, 2011) at a spectral resolution of T106 (corresponding to a horizontal grid spacing of approximately 1 • ) and on 31 vertical levels.…”
Section: Cosmo Isomentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation is performed with explicit convection at a horizontal grid spacing of 0.125 • (in rotated coordinates, corresponding to approximately 14 km) and with 60 hybrid levels in the vertical. Marsham et al (2013b), Pearson et al (2014, and Pante and Knippertz (2019) showed that explicit convection leads to a more realistic representation of the West African Monsoon already with a relatively coarse model resolution on the order of 10 km. Initial and lateral boundary conditions are provided every 6 h by the isotope-enabled global climate model ECHAM5-wiso (Werner et al, 2011) at a spectral resolution of T106 (corresponding to a horizontal grid spacing of approximately 1 • ) and on 31 vertical levels.…”
Section: Cosmo Isomentioning
confidence: 99%
“…This section focuses on investigating the large-scale flow conditions associated with the four transport pathways. Previous work has shown that even during the warm season the investigation region is frequently affected by positively tilted upper-level intrusions of high potential vorticity (PV) from higher latitudes, usually associated with Rossby wave breaking over the North Atlantic (Fröhlich and Knippertz, 2008;Papin et al, 2020). Ahead of these troughs, moist mid-level air can be transported northwards around the western flank of the anticyclone overlaying the low-level SHL and lead to precipitation in north-western Africa (Knippertz et al, 2003;Knippertz, 2003).…”
Section: Associated Large-scale Flow Conditionsmentioning
confidence: 99%
“…2) can be applied independently on the number of dimensions and can therefore be used the same way. Existing identification techniques (see an overview of them in Papin et al, 2020) rely on following the 2-PVU boundary, and searching points along this boundary meeting certain criteria. However in 3-D, there is no unique direction to follow the dynamical tropopause, making such techniques not applicable.…”
Section: Strategymentioning
confidence: 99%
“…Recently, combination of state-of-the-art interactive 3-D visualization techniques (Rautenhaus et al, 2018, provide a comprehensive survey) with 3-D detection of atmospheric features opened the door for comprehensive case studies of 3-D atmospheric dynamics (e.g., Rautenhaus et al, 2015a;Kern et al, 2018Kern et al, , 2019Bader et al, 2019). With respect to objective identification of PV structures, Papin et al (2020) recently provided an overview of identification techniques for PVSs. They classified the methods into techniques based on the reversal of the meridional PV gradient, and techniques based on distance thresholds along a 2-PVU contour.…”
mentioning
confidence: 99%
“…It occurs when the background flow is weak and the latitudinal potential vorticity (PV) gradient is small so that the waves become nonlinear and eventually break (Li et al., 2018; McIntyre & Palmer, 1983; Strong & Magnusdottir, 2008a; Tyrlis & Hoskins, 2008). Accompanied by deforming and overturning of the PV contours, the RWB leads to the exchange of heat, momentum and moisture between the tropics and extratropics (e.g., Papin et al., 2020). The occurrence of the RWB can modulate the interaction between high and low latitudes (Li et al., 2018), and it links the mid‐latitude weather systems and the Madden‐Julian oscillation (Cassou, 2008; Li et al., 2018; MacRitchie & Roundy, 2016).…”
Section: Introductionmentioning
confidence: 99%